2013
DOI: 10.3892/etm.2013.1373
|View full text |Cite
|
Sign up to set email alerts
|

In vitro studies on the cytotoxicity, and elastase and tyrosinase inhibitory activities of marigold (Tagetes erecta L.) flower extracts

Abstract: Marigold (Tagetes erecta L.) has long been used as a medicinal herb for a number of therapeutic activities. In the present study, the cytotoxicities of ethanol and ethyl acetate extracts of marigold flowers and their inhibitory effects on elastase and tyrosinase enzymes were investigated. An MTT assay was performed to measure the cytotoxicity of these two extracts on the H460 lung cancer and the Caco-2 colon cancer cell lines. An elastase assay kit, based on the digestion of a non-fluorescent elastin substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 16 publications
1
16
1
Order By: Relevance
“…A much lower amount of viable cells (less than 10%) were detected at this range of concentrations, which showed the maximum inhibition concentration. These results were in accordance with previous studies performed on T. erecta conducted by Gupta and Gupta [6], Vallisuta and Nukoolkarn [25], and Ayyadurai and Valarmathy [26]. Interestingly, the study conducted by [7] for determining the cytotoxic activity of the essential oils of four plants (T. erecta L., Tetradenia riparia, Bidens sulphurea, and Foeniculum vulgare) against six tumor cell lines murine melanoma (B16F10), human colon carcinoma (HT29), human breast adenocarcinoma (MCF-7), human cervical adenocarcinoma (HeLa), human hepatocellular liver carcinoma (HepG2), and human glioblastoma (MO59J, U343, and U251), showed that cancer cells have higher sensitivity to the oil of T. erecta.…”
Section: Cytotoxic Activitysupporting
confidence: 93%
“…A much lower amount of viable cells (less than 10%) were detected at this range of concentrations, which showed the maximum inhibition concentration. These results were in accordance with previous studies performed on T. erecta conducted by Gupta and Gupta [6], Vallisuta and Nukoolkarn [25], and Ayyadurai and Valarmathy [26]. Interestingly, the study conducted by [7] for determining the cytotoxic activity of the essential oils of four plants (T. erecta L., Tetradenia riparia, Bidens sulphurea, and Foeniculum vulgare) against six tumor cell lines murine melanoma (B16F10), human colon carcinoma (HT29), human breast adenocarcinoma (MCF-7), human cervical adenocarcinoma (HeLa), human hepatocellular liver carcinoma (HepG2), and human glioblastoma (MO59J, U343, and U251), showed that cancer cells have higher sensitivity to the oil of T. erecta.…”
Section: Cytotoxic Activitysupporting
confidence: 93%
“…The lowest IC 50 values were 7.47 ± 1.08 and 6.93 ± 0.77 g/ml for the B16F10 and HT29 cell lines, respectively, which were significantly lower than the IC 50 value obtained for the normal cell line (19.50 ± 5.96 g/ml). On the other hand, recent studies using the MTT assay reported that Tagetes erecta extracts in EtOH and EtOAc did not significantly affect the cell viability of H460 (pleural carcinoma) and Caco-2 (colon carcinoma) cells as compared with the control groups (Vallisuta et al, 2014).…”
Section: Resultsmentioning
confidence: 98%
“…[28]. The sample (20 μL), 0.1 M phosphate buffered saline (220 μL) and tyrosinase (20 μL; 1500–2000 U/mL) were mixed, 1.5 mM tyrosine solution (40 μL) was added, and the mixture was incubated for 15 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%